Predictors of prone position use in patients with COVID-19 acute respiratory distress syndrome in intensive care units: A cross-sectional study - Skarlet Marcell Vásquez; Olga Lucía Cortés; María del Pilar Paipa-Campos; Carolina Mójica-Diaz; Yudy Andrea Rojas-Castañeda; Sandra Patricia Pulido-Barragán; Martha Cecilia Arias-Portillo; Maribel Esparza-Bohorquez; Natalia Martínez; Indira Alba Arévalo-Sandoval (Tehran University of Medical Sciences, 2023)
Background & Aim: Clinical recommendations for ventilation management in patients with COVID-19 acute respiratory distress syndrome suggest the use of the prone position as a complementary therapy, however, there is wide variability in its use. The purpose of this study is to identify the predictor factors for using the prone position for patients hospitalized in intensive care units with COVID-19 acute respiratory distress syndrome. Methods & Materials: A Cross-sectional study was carried out, including adult patients with COVID-19 acute respiratory distress syndrome hospitalized in intensive care units of four hospitals in Colombia. A multiple logistic regression model was constructed in which the main outcome was the prone position in intensive care, and the independent variables included sociodemographic characteristics, history, health status, progress, and treatment. Results: A total of 473 patients were included in this study; 59.8% (n=283) received prone position therapy within 24-96 hours of hospitalization in intensive care. Out of the total of eligible variables in the logistics-regression model, factors in favor of the prone position were PCR>10mg/L (OR=3.33), private healthcare network (OR=1.99), hypertension (OR=1,76), cough or dyspnea symptoms at intensive care admission (OR=2.69 and OR=1.91), oxygen saturation <90% (OR=1.84). Factors against the prone position were heart disease (OR=0.34), FiO2>50% (OR=0.32), and TP>13 seconds (OR=0.53). Conclusion: Patients with COVID-19 acute respiratory distress syndrome with a higher probability of prone position in intensive care were those with PCR>10mg/L, cough, dyspnea, and private healthcare network. The predictors identified in this study could help standardize the prone position therapy.